The frequency of inappropriate tablet splitting in primary care - Quinzler, Renate; Gasse, Christiane; Schneider, Armin; Kaufmann-Kolle, Petra; Szecsenyi, Joachim; Haefeli, Walter E. (European journal of clinical pharmacology, 2006)
We assessed the frequency and determinants of tablet splitting in primary care in Germany and evaluated the quality of information on divisibility in the Summary of Product Characteristics (SPCs) and in the Package Leaflet (PL) as legal sources of information for health care providers and patients.
Gesehen am 12.05.2021